Composição básica da carne de suínos alimentados com rações que continham alho (Allium sativum L.) em substituição a antibiótico - Piccolo, Maria das Graças; Salustiano Pereira, Alonso; Melgaço de Andrade Costa, Paulo; Reis Condé, Alcides (Revista Ceres, 2025)
The purpose of this experiment was to study the effects of garlic (Allium sativum L.) as an antibiotic substitute, on the meat composition of pigs.